2016
DOI: 10.17265/2328-7144/2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Factors Affecting the Intention to Use Mobile Payment Services in Vietnam

Abstract: The goal of this paper is to spot out factors affecting the intention to use mobile payment service plan in Vietnam. This study attempts to analyze the impact of various variables extracted from mobility, convenience, compatibility, M-payment knowledge, ease to use, usefulness, risk, trust, and safe to use on intention to use mobile payment.Quantitative questionnaire is used to measure responses of participants. The statistical analysis method employed in this study is to apply Structural Equation Modeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 49 publications
4
12
2
2
Order By: Relevance
“…This result reflects those of Cebeci et al (2019) in their research on understanding the intention to use Netflix, who also found that knowledge is related to both PEOU and PU. They are consistent with previous research (Bailey et al, 2017;Kim et al, 2010;Liu & Tai, 2016;Sá nchez-Prieto et al, 2017). People who have self-efficacy of using Netflix or any other new technology, perceive that they can use it without having a problem.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result reflects those of Cebeci et al (2019) in their research on understanding the intention to use Netflix, who also found that knowledge is related to both PEOU and PU. They are consistent with previous research (Bailey et al, 2017;Kim et al, 2010;Liu & Tai, 2016;Sá nchez-Prieto et al, 2017). People who have self-efficacy of using Netflix or any other new technology, perceive that they can use it without having a problem.…”
Section: Discussionsupporting
confidence: 91%
“…Cebeci et al (2019) in their research on understanding the intention to use Netflix, found that knowledge is related to both PEOU and PU. Bailey et al (2017); Kim et al (2010); Liu and Tai (2016); Sá nchez-Prieto et al (2017) also found that knowledge is related to both PEOU and PU. Izuagbe et al (2019) discovered a substantial correlation between PEOU and e-Skills.…”
Section: Literature Reviewmentioning
confidence: 92%
“…Performance expectancy is found to have the most signi cant positive impact on behavioral intention because it has the highest standardized beta coe cient. From an academic viewpoint, this nding supports prior research's ndings on determinants of Vietnamese consumers' intention to adopt digital wallet services (Gia-Shie and Pham, 2016). A large number of studies R DFFHS D FH RI H SD H H R V D LJL D ZD H V D VR V RZ D LV IDF RU LV H RV signi cant determinant of consumers' use intention (Intarot and Beokhaimook, 2018).…”
Section: Performance Expectancy (Pe) and Behavioral Intention (Bi) Of...supporting
confidence: 83%
“…In short, low security and nancial risks will encourage consumers to adopt digital wallets. On the other hand, consumers will refrain from adopting LV HF R RJ LI SHUFHLYH ULVNV DUH LJ HVSL H H DE D FH RI V LHV R H L SDF RI SHUFHLYH ULVNV R EH DYLRUD L H LR to adopt e-payment methods, including digital wallets (Phan HW DO , 2020;Gia-Shie and Pham, 2016;Nguyen and Huynh, 2017), studies on this area in Vietnam is still limited. From the preceding discussion, the following hypotheses are put forth.…”
Section: Hufhl Hg Ulvnvmentioning
confidence: 99%
“…The same thing was also conveyed by Liu & Tai (2016). With the technology acceptance model (TAM) approach, he wanted to analyze the impact of various variables extracted from mobility, convenience, compatibility, mobile payment knowledge, ease to use, usefulness, risk, trust, and safe to use on Intention to use mobile payment in Vietnam.…”
Section: Literature Reviewmentioning
confidence: 99%